A model-based analysis of the German current account surplus - Dirk Bursian; Stefan Goldbach; Axel Jochem; Arne Nagengast; Matthias Schön; Nikolai Stähler; Igor Vetlov (Deutsche Bundesbank, 2020)
Germany's current account balance has been persistently high for about two decades and has increasingly attracted criticism as well as prompted proposals for policy measures geared to reducing the surplus. Assessing such proposals properly requires an analysis based on structural models. As pointed out in a recent Bundesbank monthly report and shown in more detail in this paper, model-based estimates of possible current account adjustments in Germany are subject to a substantial structural uncertainty, as point estimates vary greatly across a variety of models, with regard to both the size and the sign of the impact on the current account. Simulation exercises illustrate the cross-model differences, which could be related to the underlying modelling assumptions of each model. Overall, while several scenarios reveal scope for a significant reduction in the German current account surplus in some of the models, more precise estimates would require designing scenarios which are better tailored to the specific policy proposals and the environment in which the policy would be implemented.
Keywords: F32; E32; E1; C54; 330; current account adjustment; business cycle; aggregative models; quantitative policy modelling